PANDEMI COVID-19 DAN ADAPTASI PELAKU PARIWISATA DI DATARAN TINGGI DIENG - Ferita Nelindya Afriana; Nur Widiyanto (Kepariwisataan: Jurnal Ilmiah, 2021)
The paper aimed to find out the adaptation of tourism actors in Dieng Plateau, Central Java in dealing with the pandemi. The qualitative study through employing observation and in-depth interview as data collection techniques reveals that COVID-19 pandemic has weakened the tourism sektor in Wonosobo Regency to the lowest point in history. The pandemic’s impact has appeared on the economic and management aspects of both the government, tourism actors, and tourists. Tourism destinations in Wonosobo, especially in the Dieng Plateau, has been closed, resulting in a drastically decrease in the number of visitor, similar to the other destinations facing the huge economic losses in tourism. Through the reopening of several phases in stages with the adaptation of tourism in related tourist attractions, will save the tourism industry. So that tourism actors in Dieng included tourism sektor employees, guests, government, to adapt the pandemic have started to adapt the new behavior in tourism sectors during the crises. These adaptation strategies are expected to revive tourism sektors measured from the increase of visitor’s arrival and the implementation of the new behavior in tourism sector.Keywords: Pandemic; Dieng; Adaptation; Impact